2004
DOI: 10.1590/s1516-35982004000300012
|View full text |Cite
|
Sign up to set email alerts
|

Peso de abate de machos não-castrados para produção do bovino jovem. 1. Desempenho em confinamento e custos de produção

Abstract: Com o objetivo de obter o peso adequado de abate de machos não-castrados e a economicidade da produção do bovino jovem, foi realizado na Embrapa Pecuária Sudeste um confinamento com 234 animais cruzados Blonde d'Aquitaine x Nelore (BN), Canchim x Nelore (CN), Limousin x Nelore (LN) e Piemontês x Nelore (PN) e puros Canchim (CA) e Nelore (NE) nos anos de 1994, 1995 e 1997. Ao início do experimento, os animais apresentavam 12 meses de idade; os BN, CA, CN e LN pesavam 265 kg, os NE 214 kg e os PN 237 kg. Foram t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
(6 reference statements)
1
3
0
5
Order By: Relevance
“…Feed conversion (FC) worsened as the slaughter weight increased, corroborating the literature (Costa et al, 2002a;Arboitte et al, 2004a;Cruz et al, 2004a). Costa et al (2002a) reported that with increase in animal weight feed efficiency is lowered, and this is due to the differences in the composition of weight gain.…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…Feed conversion (FC) worsened as the slaughter weight increased, corroborating the literature (Costa et al, 2002a;Arboitte et al, 2004a;Cruz et al, 2004a). Costa et al (2002a) reported that with increase in animal weight feed efficiency is lowered, and this is due to the differences in the composition of weight gain.…”
Section: Resultssupporting
confidence: 80%
“…This demonstrates that there is variation in ingestion and that other factors, such as genetics, weight at maturity and type of diet, can interfere with this parameter. Reduction in DMIBW between the slaughter weight from 400 to 480 for animals of different genetic groups was reported by Cruz et al (2004a). However, Mello (2007) did not observe difference for DMIBW when slaughtering crossbred Red Angus or Blonde D'Aquitaine with Nellore at 480, 520 and 560 kg body weight.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Mesmo com longo período médio de confinamento (170 dias), o percentual atribuído ao volumoso foi baixo e decorrente dos custos de produção menores que os de mercado, por peculiaridades da fazenda e, principalmente, em razão do custo da adubação. Cruz et al (2004), que avaliaram rentabilidade mensal de animais em confinamento com 12 meses de idade, para três pesos ao abate (400, 440 e 480kg), dos grupos genéticos 1/2 Blonde d'Aquitane x 1/2 Nelore (1,9; 1,8 e 1,3%), 1/2 Limousin x 1/2 Nelore (2,2; 2,6 e 1%), 1/2 Piemontês x 1/2 Nelore (1,1; 0,7 e 0,8%), Canchim (1,2; 0,2 e 0,2%), 1/2 Canchin x 1/2 Nelore (0,9, -0,3 e 0,6%) e Nelore (-1,1, -1,2 e -1,1%), respectivamente. Os resultados demonstram maior rentabilidade nos menores pesos de abate.…”
Section: Resultsunclassified